Circumpolar Biodiversity Monitoring Program Framework Document - Petersen, Aevar; Zöckler, Christoph; Gunnarsdóttir, María Victoria (Conservation of Arctic Flora and Fauna (CAFF), 2004)
Discusses the history, purpose, approach perspectives, development and action plan for the Circumpolar Biodiversity Monitoring Program (CBMP).